Regionalny poradnik genealogiczny – kwerendy i ich wyniki na przykładzie badań autora dotyczących Uniejowa i okolic - Szkutnik, Piotr (Biuletyn Uniejowski, 2014)
The author’s ancestors lived in Uniejów and its region as early as the end of the 18th and in the 19th century. The ascendents of his mother living at the turn of the 18th century were sheep-farmers, of whom the Wiśniewski family lived first in Brudzew, and then their son Marcin in Milejów. The Rosiński family lived in Uniejów and later in Czepów Górny and Chorzepin. Their daughter Monika lived at the beginning of the 19th century in Rożniatów in Wielenin parish, and then moved with her husband Marcin to Zieleń near Spicymierz, where their daughter was born. The ancestors of the author’s father were burghers. The Krąkowski family lived in Wilamów in the years 1857−1863. In 1859 Antonina Krąkowska married Julian Godziński in Wilamów. Later the above mentioned families left the region of Uniejów.